2013
DOI: 10.1007/s10103-013-1371-9
|View full text |Cite
|
Sign up to set email alerts
|

LED therapy or cryotherapy between exercise intervals in Wistar rats: anti-inflammatory and ergogenic effects

Abstract: The aim of this study was to test, between two bouts of exercise, the effects of light-emitting diode (LED) therapy and cryotherapy regarding muscle damage, inflammation, and performance. Male Wistar rats were allocated in four groups: control, passive recovery (PR), cryotherapy (Cryo), and LED therapy. The animals were submitted to 45 min of swimming exercise followed by 25 min of recovery and then a second bout of either 45 min of exercise (muscle damage analysis) or time to exhaustion (performance). During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 35 publications
0
9
0
2
Order By: Relevance
“…[4][5][6][7][8] There were no studies found in the literature search that supported cryotherapy over PBMT. The PBMT was more effective in preventing increases in CK levels, 4-8 blood lactate, 5 C-reactive protein, 5,7 and inflammation 6,7 after an exercise bout. In addition, PBMT was able to increase time to exhaustion 7 and better maintain muscular strength following strenuous exercise 4,8 compared with cryotherapy.…”
Section: Best Evidencementioning
confidence: 83%
See 2 more Smart Citations
“…[4][5][6][7][8] There were no studies found in the literature search that supported cryotherapy over PBMT. The PBMT was more effective in preventing increases in CK levels, 4-8 blood lactate, 5 C-reactive protein, 5,7 and inflammation 6,7 after an exercise bout. In addition, PBMT was able to increase time to exhaustion 7 and better maintain muscular strength following strenuous exercise 4,8 compared with cryotherapy.…”
Section: Best Evidencementioning
confidence: 83%
“…This was demonstrated by an increase of CK, blood lactate, and frequency of necrosis, measured by histological analysis, in placebo treatments, 4,5,8 an ice bag application, 4,8 and coldwater immersion therapy. 5,7 Compared with placebo treated groups, cryotherapy demonstrated no difference in CK 4,5,8 or blood lactate 5 levels at any time points. PBMT protected the muscle against damage in the included studies, with significantly lower levels of muscle damage markers [4][5][6][7][8] ; thus, inflammation markers of c-reactive protein [5][6][7] and leukocyte analysis 6,7 were also lower in groups treated with PBMT.…”
Section: Best Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Nós aplicamos um comprimento de onda de 940 nm devido ao fato de que maiores comprimentos de onda penetram com maior profundidade no tecido muscular 55 . Prévios estudos mostraram que esse comprimento de onda após exercísio intenso em modelos animais foi capaz de diminuir dano muscular e os processos infl amatórios que ocorrem após exercício intenso 45,56 . As limitações do presente estudo foram o nú-mero pequeno de participantes o qual talvez tenha limitado o poder das análises estatísticas; a falta de medidas diretas da carga externa, como por exemplo, a distância em alta intensidade durante os treinos coletivos e o amistoso (TABELA 2); e a falta de medidas de desempenho ao fi nal da semana de treino.…”
Section: Discussionunclassified
“…Another study observed a reduction in CK activity when LLLT was applied after exercises in a model of swimming with workload [17]. Recently, LLLT using LEDs (LEDT) has demonstrated similar benefits to decrease CK activity when applied after exercise [35] or during rest intervals between bouts of physical activity [36]. All these studies assessed CK activity after 24 h or during a time range of 24-48 h after the exercise.…”
Section: Discussionmentioning
confidence: 99%